Anti-wrinkle Finishing of Cotton Fabrics with Pyromellitic Acid Enhanced by Polyol Extenders - QI Huan; MENG Lujie; LIN Xiaofang; XU Wanwan; CHEN Yangyi; ZHANG Chuyang; QIU Yiping (东华大学学报（英文版）, 2022)
TS195; Pyromellitic acid (PMA) has been employed for formaldehyde-free anti-wrinkle finishing on cotton fabrics for its low damage to fibers and absence of phosphorus-containing catalysts. However, the wrinkle resistance performance of fabrics failed to meet the application expectation. In this work, the polyol extenders were introduced into PMA cross-linked cellulose for further improving fabric resilience by a two-step dipping-squeezing-curing method. Eleven polyols were employed as the chain extenders for PMA anti-wrinkle finishing on fabrics, among which sorbitol presented the best chain-spreading effect on wrinkle resistance. After screening the process parameters, the optimum process was obtained as follows. The dosage ratio of PMA to sorbitol was 1:1, the curing condition was 150-160 ℃ for 2-3 min. Scanning electron microscopy (SEM), thermogravimetric analysis(TGA) and Fourier transform infrared(FTIR) spectroscopy were employed to characterize the fiber changes during the process. The results showed that the sorbitol incorporation could facilitate the remelting and redissolution of PMA on fiber surface. During the curing process, sorbitol could form ester linkages between PMA molecules and improve the fiber resilience. The treated samples presented excellent washing durability, and the wrinkle recovery angle Aw was still 265.1° after 10 washes, which was close to that of 1, 2, 3, 4-butane tetracarboxylic acid (BTCA) but with lower tearing load loss. The results provide new insights for the application of PMA in formaldehyde-free anti-wrinkle finishing on cotton fabrics.